Предмет: Алгебра,
автор: dontcrybaby
sin(p/4-a)sin(p/4+a) -cos(p/4+a)cos(p/4-a) ПОМОГИТЕ СРОЧНО!
Ответы
Автор ответа:
1
Ответ:
0
Объяснение:
sin(π/4-a)sin(π/4+a) - cos(π/4+a)cos(π/4-a) =
= -(cos(π/4+a)cos(π/4-a) - sin(π/4-a)sin(π/4+a))=
= - cos(π/4+a+π/4-a) = - cos(2π/4) = - cos(π/2) = - 0 = 0
Используем формулу косинуса разности
dontcrybaby:
это какая,напишите пожалуйста
Похожие вопросы
Предмет: Геометрия,
автор: staslondar119
Предмет: Математика,
автор: holyakanna
Предмет: Геометрия,
автор: grigorevakristina461
Предмет: Математика,
автор: valeriatkach
Предмет: Математика,
автор: юляшка5551